The relationship between Digital Literacy Skills, Learning Instruments, Culture and Student Motivation among Indigenous students in Malaysia / Nur 'Ainaa Abdul Rahim ... [et al.] - Abdul Rahim, Nur 'Ainaa; Mohamed Shuhidan, Shamila; Husaini, Haslinda; Siti Khadijah, Ute Lies; Bidin, Mohd Arif Fahmi (Faculty of Information Management, 2023)
The Malaysian Ministry of Education (MoE) integrated the Orang Asli Education Transformation Plan in the Malaysia Education Blueprint 2013-2025 and implemented the Primary Literacy and Numeracy programme (PLaN) in indigenous schools in Malaysia. However, according to a report, indigenous student (IS) dropout rates from schools grew considerably to 26% in 2017. IS's feelings about living with their community are the reason why some them having low motivation to attend to school and overlook their education. Therefore, the objective of this study is to examine the relationship between digital literacy skills, learning instruments and culture toward student motivation among IS in Malaysia. A survey questionnaire used to measure the relationship between the variables. Using SmartPLS to analyse the data, it found that two hypotheses were supported: Learning Instruments (t- 3.196, p = <0.001) and Culture (t-1.807, p = <0.036) significantly related with student motivation among IS. The significance of the research is to assist IS in improving sustainability learning so that they can improve quality of life. Hence it can give a guideline to the policymaker to produce a quality education especially for IS and to support the UNESCO initiative Sustainable Development Goal 4, Quality of Education.